Laboratory filter paper as a substrate material for flexible supercapacitors. Issue 1 (26th October 2017) - Zhang, Leicong; Yu, Xuecheng; Zhu, Pengli; Zhou, Fengrui; Li, Gang; Sun, Rong; Wong, Ching-ping
Abstract : A lightweight flexible asymmetrical all solid-state supercapacitor based on common laboratory filter paper has been built and exhibits excellent electrochemical and mechanical flexibility performance. Abstract : In this study, a flexible asymmetrical solid-state filter paper-based supercapacitor was fabricated. Common laboratory filter paper (FP) provides toughness and flexibility to the whole device. Simply, traditional electroless Ni plating and electro-deposition were introduced to change the electrical conductivity of FP as a flexible and conductive substrate material. Then, the electrochemical active material Co(OH)2 and active carbon (AC) were respectively coated on the conductive Ni paper through electro-deposition and physical coating methods to prepare Ni/Co(OH)2 -FP as a positive electrode and Ni/AC-FP as a negative electrode. Moreover, they were separated by a piece of FP coated with an ionic gel electrolyte to assemble the flexible asymmetrical solid-state supercapacitors. This supercapacitor exhibits superior flexibility, large volume energy density (0.64 mW h cm −3 ), and good bending cycle performance (95.89% capacitance retention after 500 bending cycles). It has been demonstrated that the assembled supercapacitor can still power a red light-emitting diode (LED) indicator normally regardless of the bending state and bending frequency. This study may provide promising insights for the design and fabrication of a flexible asymmetrical solid-state supercapacitor in a flexible power supply for wearable and portable applications.